2021
DOI: 10.1021/acs.molpharmaceut.1c00553
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein (ABCB1/MDR1) Controls Brain Penetration and Intestinal Disposition of the PARP1/2 Inhibitor Niraparib

Abstract: Niraparib (Zejula), a selective oral PARP1/2 inhibitor registered for ovarian, fallopian tube, and primary peritoneal cancer treatment, is under investigation for other malignancies, including brain tumors. We explored the impact of the ABCB1 and ABCG2 multidrug efflux transporters, the OATP1A/1B uptake transporters, and the CYP3A drug-metabolizing complex on oral niraparib pharmacokinetics, using wild-type and genetically modified mouse and cell line models. In vitro, human ABCB1 and mouse Abcg2 transported n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The five PARP inhibitors are substrates for P-gp and BRCP. In a DDI study, P-gp and BRCP inhibitors did not have any significant impact on the systemic exposure of olaparib, niraparib and veliparib, but significantly increased their brain accumulation, indicating that P-gp and BRCP inhibitors may improve treatment outcomes when co-administered with olaparib, niraparib or veliparib in patients with brain tumors (34,37,57). For rucaparib and talazoparib, P-gp and BRCP have critical roles in their systemic exposure and brain accumulation, indicating that dose adjustment or caution is required when rucaparib and talazoparib are co-administered with strong P-gp and BRCP inhibitors or inducers (43,51,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The five PARP inhibitors are substrates for P-gp and BRCP. In a DDI study, P-gp and BRCP inhibitors did not have any significant impact on the systemic exposure of olaparib, niraparib and veliparib, but significantly increased their brain accumulation, indicating that P-gp and BRCP inhibitors may improve treatment outcomes when co-administered with olaparib, niraparib or veliparib in patients with brain tumors (34,37,57). For rucaparib and talazoparib, P-gp and BRCP have critical roles in their systemic exposure and brain accumulation, indicating that dose adjustment or caution is required when rucaparib and talazoparib are co-administered with strong P-gp and BRCP inhibitors or inducers (43,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Niraparib is a substrate for P-gp and BCRP; its major primary metabolite M1 is a substrate for MATE1 and MATE2-K (37). In vitro studies have indicated that P-gp and BCRP do not have any significant impact on the bioavailability and liver disposition of niraparib (37). However, P-gp and BCRP may significantly increase the brain distribution of niraparib.…”
Section: Transporter-mediated Ddis Involving Parp Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the two was first discovered by Rottenberg et al The group’s experiments demonstrated that in a breast tumor model, the emergence of PARPi-acquired resistance is related to upregulation of P-gp expression, and that the P-gp inhibitor tariquidar can reverse its overexpression ( Rottenberg et al, 2008 ). Similarly, in vitro experiments by Margarida et al demonstrated that ABCB 1a/1b attenuated brain penetration and promoted systemic elimination of niraparib in mice, with partial reversal of resistance following treatment with the ABCB1 inhibitor Elacridar (F. Martins et al, 2021 ). A clinical study (NCT02681237) found that ABCB1 was upregulated in 15% of patients in the progression group after using PARPi.…”
Section: Mechanisms Of Resistance To Parp Inhibitorsmentioning
confidence: 92%
“…It has a very wide substrate specificity, and it is highly expressed in many tumors, especially in drug-resistant breast cancer and OC ( Christie et al, 2019 ). With the up-regulation of ABCB 1a/1b genes, the expression of P-gp efflux transporter increases, resulting in a decrease in the effective intracellular drug concentration, thus, leading to PARPi resistance (F. Martins et al, 2021 ). In 2020, a quantitative mass spectrometry imaging (LC-MS/MS) assay showed that in a P-gp-overexpressing ovarian cancer model, niraparib was unevenly distributed within the tumor, reducing the efficacy of drug treatment; thus, suggesting that it is resistant to PARPi( Morosi et al, 2020 ).…”
Section: Mechanisms Of Resistance To Parp Inhibitorsmentioning
confidence: 99%